Economic and institutional analyses of soil conservation projects in Central America and the Caribbean - Lutz, Ernst ed. (World Bank WashingtonUS, 1994)
Seeks to analyze soil degradation and conservation in Central America and the Caribbean objectively. Uses a cost-benefit approach to analyze soil degradation problems and the cost-effectiness of proposed solutions. Focuses on the profitability of conservation measures and the constraints to their adoption from the farmer's perspective.